Inequalities in glycemic and multifactorial cardiovascular control of type 2 diabetes: The Heart Healthy Hoods study - Ares-Blanco, Sara; Polentinos-Castro, Elena; Rodríguez-Cabrera, Francisco; Gullón, Pedro; Franco, Manuel; del Cura-González, Isabel (Frontiers in Medicine, 2022)
Aim This study aimed to analyze glycemic control and multifactorial cardiovascular control targets in people with type 2 diabetes (T2DM) in primary care according to sex and socioeconomic status (SES). Materials and methods This is an observational, cross-sectional, and multicenter study. We analyzed all the patients with T2DMM aged between 40 and 75 years in Madrid city (113,265) through electronic health records from 01 August 2017 to 31 July 2018. SES was defined by an area-level socioeconomic index stratified by quintiles (1st quintile: more affluent). Outcomes Outcomes included glycemic control (HbA1c ≤ 7%), 3-factor cardiovascular control [HbA1c ≤ 7%, blood pressure (BP), < 140/90 mmHg, LDL < 100 mg/ml] and 4-factor control [HbA1c ≤ 7%, blood pressure (BP) < 140/90 mmHg, LDL < 100 mg/ml, and BMI < 30 kg/m2]. Multilevel logistic regression models analyzed factors associated with suboptimal glycemic control. Results In total 43.2% were women. Glycemic control was achieved by 63% of patients (women: 64.2% vs. men: 62.4%). Being more deprived was associated with suboptimal glycemic control (OR: 1.20, 95% CI: 1.10–1.32); however, sex was not related (OR: 0.97, 95% CI: 0.94–1.01). The optimal 3-factor control target was reached by 10.3% of patients (women: 9.3% vs. men: 11.2%), especially those in the 5th quintile of SES. The 4-factor control was achieved by 6.6% of the sample. In the 3-factor control target, being women was related to the suboptimal 3-factor control target (OR: 1.26, 95% CI: 1.19– 1.34) but only belonging to SES 4th quintile was related to the unachieved target (OR: 1.47, 95% CI: 1.04–2.07). Conclusion Suboptimal glycemic control was associated with being less affluent and suboptimal 3-factor control target was associated with being women.